2018
DOI: 10.1016/j.immuni.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Endoplasmic Reticulum Contact Sites Function as Immunometabolic Hubs that Orchestrate the Rapid Recall Response of Memory CD8+ T Cells

Abstract: Glycolysis is linked to the rapid response of memory CD8 T cells, but the molecular and subcellular structural elements enabling enhanced glucose metabolism in nascent activated memory CD8 T cells are unknown. We found that rapid activation of protein kinase B (PKB or AKT) by mammalian target of rapamycin complex 2 (mTORC2) led to inhibition of glycogen synthase kinase 3β (GSK3β) at mitochondria-endoplasmic reticulum (ER) junctions. This enabled recruitment of hexokinase I (HK-I) to the voltage-dependent anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 59 publications
6
114
0
Order By: Relevance
“…While effector T cells induce aerobic glycolysis, it was shown that memory T cells instead rely on mitochondrial metabolism and lipid oxidation 18,19 but can rapidly revert to glycolysis upon restimulation through endoplasmic reticulummitochondrial direct interactions that serve as metabolic hubs. 20 Unlike effector T cell subsets, regulatory T cells (Tregs) do not require GLUT1 or high levels of glutamine uptake through the amino acid transporter ASCT2 21,22 and instead predominantly rely on mitochondrial lipid, pyruvate, and lactate oxidation. 10,[23][24][25] Tregs can be highly glycolytic, but the primary Treg transcription factor, FoxP3, has also been shown to repress glycolysis and high rates of glucose metabolism can impair Treg suppressive capacity.…”
Section: Ba S Ic Mechanis Ms That Reg Ul Ate Immune Me Tabolis Mmentioning
confidence: 99%
“…While effector T cells induce aerobic glycolysis, it was shown that memory T cells instead rely on mitochondrial metabolism and lipid oxidation 18,19 but can rapidly revert to glycolysis upon restimulation through endoplasmic reticulummitochondrial direct interactions that serve as metabolic hubs. 20 Unlike effector T cell subsets, regulatory T cells (Tregs) do not require GLUT1 or high levels of glutamine uptake through the amino acid transporter ASCT2 21,22 and instead predominantly rely on mitochondrial lipid, pyruvate, and lactate oxidation. 10,[23][24][25] Tregs can be highly glycolytic, but the primary Treg transcription factor, FoxP3, has also been shown to repress glycolysis and high rates of glucose metabolism can impair Treg suppressive capacity.…”
Section: Ba S Ic Mechanis Ms That Reg Ul Ate Immune Me Tabolis Mmentioning
confidence: 99%
“…Initial studies highlighting the importance of the transition from highly anabolic effector T‐cell populations to more quiescent memory T populations, demonstrated that development of memory T‐cell populations in mice were contingent on the limitation of aerobic glycolysis and the engagement of mitochondrial OXPHOS . Robust mitochondrial metabolism has also been linked to rapid recall abilities of memory T cells following antigen restimulation …”
Section: Memory T Cells and Mitochondrial Metabolismmentioning
confidence: 99%
“…2,24 Robust mitochondrial metabolism has also been linked to rapid recall abilities of memory T cells following antigen restimulation. 52,53 Memory T cells have distinct mitochondrial morphology from effector T cells, which can contribute to their metabolism and function. Both T CM and IL-15 derived memory T cells have tighter cristae formation, 54 which has been linked to more efficient OXPHOS.…”
Section: Memory T Cells and Mitochondrial Metabolismmentioning
confidence: 99%
“…Bantug et al . have shown that memory CD8+ T cells use mitochondria–ER contact sites as a hub to drive rapid glycolytic remodelling, facilitating the increase in demand for glucose oxidation after IFNγ stimulation in response to an infection . The ER acts as a scaffold in this set‐up: it positions mTORC2‐AKT signalling so that pAKT can phosphorylate and inhibit GSK3β.…”
Section: Beyond the Er: Reaching Out To The Plasma Membrane And Mitocmentioning
confidence: 99%
“…Immunologists have recently turned their attention ERmitochondrial contact sites too, having appreciated that metabolic reprogramming can control the activation of T lymphocytes and influence their development into either regulatory or cytotoxic/helper effector subtypes [57]. Bantug et al have shown that memory CD8+ T cells use mitochondria-ER contact sites as a hub to drive rapid glycolytic remodelling, facilitating the increase in demand for glucose oxidation after IFNc stimulation in response to an infection [58]. The ER acts as a scaffold in this set-up: it positions mTORC2-AKT signalling so that pAKT can phosphorylate and inhibit GSK3b.…”
Section: Beyond the Er: Reaching Out To The Plasma Membrane And Mitocmentioning
confidence: 99%